The Triple Helix and The Innovation Capability: A Conceptual Framework for Creative Economic Marketing - Nuryadi Wijiharjono (Universitas Muhammadiyah Prof. DR HAMKA., 2021)
In essence, the concept of the Triple Helix describes a model of the cooperative relationship between universities, industry, and government. The purpose of this study is to formulate a conceptual framework for the relationship between institutions in the Triple Helix for improving the development of innovation capabilities to obtain a high marketing performance in creative-economy SMEs. The method used in this study is a systematic review with a resource-based view (RBV) perspective based on authoritative, relevant, and up-to-date reference sources. This study attempts to identify the main factors that influence innovation capabilities and marketing performance and to describe the complexity of various concepts, such as the concepts of intellectual capital, innovation capabilities, and creative economy, to create a comprehensive, logical, and methodical conceptual framework. This study contributes to the marketing management literature by developing the Triple Helix model to build innovation capabilities and marketing performance.